2014
DOI: 10.15274/inr-2014-10056
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment in Spinal Perimedullary Arteriovenous Fistula

Abstract: This study includes 20 patients with 21 spinal perimedullary fistulae. There were nine Type IVa (42.8%) lesions, ten Type IVb (47.6%) and two Type IVc (9.5%) lesions. The dominant arterial supply was from the anterior spinal artery (47.6%), posterior spinal artery (19%) and directly from the radiculomedullary artery (28.5%). Sixteen lesions in 15 patients were treated by endovascular route using n-butyl-2-cyanoacrylate. Endovascular treatment was not feasible in five patients. Of the ten patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 15 publications
(27 reference statements)
0
20
0
Order By: Relevance
“…In this case, surgical excision is often preferred. For example, the interventional treatments of 20 PMAVF patients described by Phadke et al (most with types A or B PMAVFs) were generally unsuccessful because the feeding arteries were too thin or tortuous; however, surgical treatment was successful (58). The key purpose of surgical treatment for spinal cord PMAVFs is to locate the fistula orifice and to remove or close it.…”
Section: Surgical Removalmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, surgical excision is often preferred. For example, the interventional treatments of 20 PMAVF patients described by Phadke et al (most with types A or B PMAVFs) were generally unsuccessful because the feeding arteries were too thin or tortuous; however, surgical treatment was successful (58). The key purpose of surgical treatment for spinal cord PMAVFs is to locate the fistula orifice and to remove or close it.…”
Section: Surgical Removalmentioning
confidence: 99%
“…These authors suggested that endovascular NBCA glue embolization is safe and efficacious for treating type B and C PMAVFs and should be considered the first option for treatment. The use of NBCA is also feasible in many type A lesions (58). A new NBCA product is Glubran, which is also a good choice.…”
Section: Endovascular Embolizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] For example, winter wheat leaves exhibit increased expression levels of key flavonoid genes and total flavonoid content in response to drought stress. [5] In the leaves of Ziziphus jujuba var. spinose, the total flavonoid content increased significantly under moderate drought treatment.…”
Section: Introductionmentioning
confidence: 99%
“…PMAVFs, or type IV arteriovenous malformations, are intradural spinal vascular abnormalities (in contrast to dural arteriovenous fistulas) that lack a nidus (as opposed to type II-III arteriovenous malformations) 2,3 .…”
mentioning
confidence: 99%